Peran Pemerintah Daerah dan Pemberdayaan Masyarakat dalam penyelenggaraaan Event Daerah Di Desa Baloli Kabupaten Luwu Utara - Andi Hasbi (Jurnal Ilmu Pemerintahan Suara Khatulistiwa, 2023)
Abstract The Role of Local Government and the Community in Involving Village Officials and the Local Government, Academics, and Society in Supporting the Cultural Event "Masamba Fair 2023" amidst Changing Societal Trends and Technological Advancements. The government plays a significant role in supporting the cultural event "Masamba Fair 2023" by involving village officials, the local government, academics, and society. This event aims to incorporate unique cultural practices, traditions, and expressions within the community, driven by changing societal trends and technological advancements. The research employed a qualitative descriptive approach, utilizing observation, interviews, and documentation. The findings highlight the training program that covers various aspects such as event operations and equipment, event ideas and concepts, and supporting cultural events. During the training, participants are trained to organize and design outbound activities and camps. This training aims to enhance their capabilities and skills. The accompanying initiatives for the Masamba Fair encourage the local government and the community to continually improve their capabilities and foster innovation to welcome future and sustainable events. This collaboration ensures the event's continuous success and sustainability. Keywords: Cultural Event, technical guidance, outbound.